Transanal hemorrhoidal desarterization under ultrasound rectodopplerometry control in surgical treatment of hemorrhoids - A. A. Nykonenko; G. I. Okhrimenko; E. I. Haidarzhi; N. G. Golovko; I. V. Zubryk; V. A. Grushka; T. V. Gurov; A. S. Aleksandrov (Клінічна хірургія)
Objective. To study the immediate and late follow-up results of treatment in patients, suffering hemorrhoids, to whom transanal hemorrhoidal desarterization under ultrasound rectodopplerometry control was done, and to compare them with results of treatment in patients, operated in accordance to procedure of standard hemorrhoidectomy.